DAMPAK TEKNOLOGI AI TERHADAP POLA KEJAHATAN - Peter Guntara; Erlinda Putri Nurdiyanti; Ratna Wulan Valentina (Jurnal Riset Multidisiplin Edukasi, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed the patterns of modern crime, particularly in the realm of cybercrime. This study aims to analyze how AI has changed the modus operandi of cyber offenses and to identify the legal challenges and enforcement strategies in addressing AI-driven crimes. This research employs a normative legal method using statutory and conceptual approaches, examining relevant regulations such as the Electronic Information and Transactions Law, the Personal Data Protection Law, and the National Cybersecurity Strategy. The findings reveal that AI has accelerated, expanded, and personalized cyberattacks through technologies such as deepfake, machine learning-based phishing, and adaptive malware. AI-related crimes complicate legal proceedings since electronic evidence can be easily manipulated and is difficult to authenticate. The main challenges lie in the lack of regulation regarding algorithmic accountability, limited digital forensic capacity, and weak international coordination. Therefore, legal reform is required to incorporate the principle of vicarious liability for AI developers, establish a specialized unit for AI-related crimes, and strengthen technology-based law enforcement capacity.